2018
DOI: 10.1155/2018/1925619
|View full text |Cite
|
Sign up to set email alerts
|

Blood Groups Distribution and Gene Diversity of the ABO and Rh (D)Lociin the Mexican Population

Abstract: Objective To determine the frequency and distribution of ABO and Rh (D) antigens and, additionally, investigate gene diversity and the structure of Mexican populations. Materials and Methods Blood groups were tested in 271,164 subjects from 2014 to 2016. The ABO blood group was determined by agglutination using the antibodies anti-A, Anti-B, and Anti-D for the Rh factor, respectively. Results The overall distribution of ABO and Rh (D) groups in the population studied was as follows: O: 61.82%; A: 27.44%; B: 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
9
19
2
2
Order By: Relevance
“…In this study, we investigated whether blood type is relevant for need for mechanical ventilation and/or morality. Therefore, we retrospectively reviewed clinical data of 90 critically ill patients who were positive for the new virus with the mean age of 58 years old (13.9) which is in agreement with most of studies conducted over patients with COVID-19 where mean age of patients with COVID-19 ranged between 53 and 73 years [ 8 - 12 ]. Moreover, in this study, we found that people with blood groups O, A, B and AB were 45.6%, 22.2%, 26.7% and 5.6%, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, we investigated whether blood type is relevant for need for mechanical ventilation and/or morality. Therefore, we retrospectively reviewed clinical data of 90 critically ill patients who were positive for the new virus with the mean age of 58 years old (13.9) which is in agreement with most of studies conducted over patients with COVID-19 where mean age of patients with COVID-19 ranged between 53 and 73 years [ 8 - 12 ]. Moreover, in this study, we found that people with blood groups O, A, B and AB were 45.6%, 22.2%, 26.7% and 5.6%, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, blood type distribution is less affected by selection biases, because apheresis donors are not selected based on their blood type. In our study, the distribution of ABO and Rh blood systems was consistent with the reported for the Mexican population 19 …”
Section: Discussionsupporting
confidence: 91%
“…14,16,17 Similar results were found in various studies conducted around the world which have revealed that blood group O is the commonest blood group while blood group AB is the rarest one. [18][19][20][21][22][23][24][25] In India, B is the second commonest blood group, which is similar to our finding. 18 Blood group A has been reported as the second commonest blood group after O in many countries like Iraq, Iran, Libya, Mauritania, Cameroon, Morocco and Mexico.…”
Section: Discussionsupporting
confidence: 84%